The Effect of Institutional Quality and Macroeconomics Variables on Non-Performing Loans in Developing Countries - Fajariyanto, Muhammad Bagja; Wasiaturrahma, Wasiaturrahma (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2024)
This study intends to examine how institutional quality and macroeconomic factors affect non-performing loans within developing countries in 2010–2019. The estimation results employing the Generalized Method of Moment (GMM) method reveal that the institutional quality variable with a proxy for the government effectiveness index and regulatory quality index has a significant effect with a negative coefficient on the non-performing loans ratio (NPL). Moreover, macroeconomic variables such as inflation, unemployment, and real interest rates significantly affect NPL. In contrast, economic growth has a significant negative effect on NPL. Policymakers should focus on creating effective regulations to reduce NPLs. The government can make clear, consistent, and transparent regulations to promote a strong and competitive private sector.